AFIKS INFLEKSI BAHASA INGGRIS DALAM NOVEL ANNA KARENINA KARYA LEO TOLSTOY - DUWIT, NOVALIA; LASUT, THERESIA M.C.; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
AFIKS INFLEKSI BAHASA INGGRIS DALAM NOVEL ANNA KARENINA KARYA LEO TOLSTOY Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dra. Theresia M.C. Lasut, M.Hum Dr. Rina P. Pamantung, M.Hum Â ABSTRACT This research with entitled : Inflectional affixes in the Novel â€œAnna Kareninaâ€ by Leo Tolstoy. The aims of this research are to identify and to analyze the kinds of inflectional affixes in the novel by using Oâ€™grady and Dobrovolskyâ€™s theory. The method used in this investigation is descriptive. The data was taken from the novel Anna Karenina by collecting and classifying them according to those forms, functions, and meanings. Â There are two significant contributions, theoretically, this written work is intented to supplement to the literature through morphology analysis and to help the students of English Department in understanding the inflectional affixes of literary work. Practically, this study helps the students or readers to known the kinds of inflectional affixes in the novel Anna Karenina through linguistics aspect, so they can understand the literary work more easily. The results of this research are directed to nouns, verbs and adjectives. The noun has 68 sentences with plural and possession, the verb has 309 sentences with third singular person, present participle, past tense, and past participle and adjective has 11 sentences with comparative and superlative. Â Keywords: Inflectional affixes, nouns, verbs, adjectives, novel, Anna Karenina